2013 IEEE International Conference on Distributed Computing in Sensor Systems 2013
DOI: 10.1109/dcoss.2013.62
|View full text |Cite
|
Sign up to set email alerts
|

Coordinates Determination of Submerged Sensors Using Cayley-Menger Determinant

Abstract: This paper investigates the problem of localizing submerged sensors and provides a new mechanism to determine the coordinates of those sensors using only one beacon node. In underwater wireless sensor networks (UWSN), precise coordinate of the sensors that actuate or collect data is vital, as data without the knowledge of its actual origin has limited value. Mostly, multilateration technique is used to determine the location of the sensors with respect to three or more known beacon nodes where distance between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The complexity of the simulated environment is discussed as well as positional errors for sensors have been elaborated in Table III. In [6], coordinates of the sensors with respect to beacon has been shown. With the simulated environment, it is possible to determine 3D coordinates of the sensors with bearing information; as the beacon is at the surface of the water, the coordinates could be known by GPS.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of the simulated environment is discussed as well as positional errors for sensors have been elaborated in Table III. In [6], coordinates of the sensors with respect to beacon has been shown. With the simulated environment, it is possible to determine 3D coordinates of the sensors with bearing information; as the beacon is at the surface of the water, the coordinates could be known by GPS.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Guevara et al proposed a closed-form method where positions of nodes are not required to localize multiple static reference nodes in [4]; distances between mobile nodes and static reference nodes are sufficient for the proposed method. Recently, the preciseness of the model with Euclidean distances between beacon and sensors has been elaborated in [6]. The paper showed that the produced negligible errors were due to linearization process of the method.…”
Section: Related Workmentioning
confidence: 99%
“…In order to validate the mathematical model, the proposed method has been simulated using Matlab in the previous paper [11]. To get distance measurement from six different positions of the beacon, it has been moved around in six different coordinates randomly within close proximity.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…All these and many other practical factors make underwater systems behave very differently from the conventional environment. Typical cases are underwater surveillance, marine ecology, and offshore exploration [6]. • Extending the use of smart sensors in the ground, hidden, or covered in other places can enable many new and advanced applications such as securing mines and improved agriculture where such uses of strong cover create EE conditions [7].…”
Section: B Unconventional Wireless Sensingmentioning
confidence: 99%